About hematology and particularly the excretion of bilirubin in Monge's disease (Soroche Chronic) - Urteaga, Oscar (1942)
The author has studied four cases of Monge´s disease (Chronic Mountain Sickness), from the hematologic point of view, mostly the bilirubin excretion. He has confirmed Hurtado´s conclusions regarding some aspects of the blood at high altitude. There is polycythemic hypervolemia. The polycythemia is macrocytic and hypocromic. The macrocitosis is mainly due to an increase in the diameter with slight diminution of the spheric index. It is therefore, a flat erythrocyte. The capacity of bilirubin excretion, is retarded in the severer cases, and particularly in those complicated with pneumoconiosis. In average cases, he believes there is a special level of blood bilirubin, higher than at sea level. After 80 days of being at sea level, he found an almost complete remission of all hematologic and clinic symptoms, as well as an improvement function.